GENOTOXIC AND HISTOPATHOLOGICAL EFFECTS OF CADMIUM IN MALE SWISS ALBINO MICE, MUS MUSCULUS - K. MOHAPATRA, ANIMESH; DATTA , SHIVIKA; KUMARI, POONAM (The Bioscan, 2013)
Oral administration of cadmium chloride caused DNA damage in the tissues of testes, liver and kidneys. Marked changes in the histological architecture of these organs were observed. Distortion of seminiferous tubules, desquamation of spermatogonia, spermatocytes and spermatids with cytoplasmic vacuolization and nuclear fragmentation in testes; disruption in arrangement of hepatic plates, widespread fibrosis, interstitial mononuclear cellular infiltration and hemorrhagic spots with necrotic hepatocytes having pycnotic nuclei in the liver and severe multifocal cloudy, hydropic degeneration with loss of cellular integrity in the renal tissues were observed. It was observed that the severity of pathological effects was dependent on the duration of post treatment period.